2019
DOI: 10.1001/jamadermatol.2019.2613
|View full text |Cite
|
Sign up to set email alerts
|

Development or Exacerbation of Head and Neck Dermatitis in Patients Treated for Atopic Dermatitis With Dupilumab

Abstract: The efficacy and safety of dupilumab, a humanized monoclonal antibody targeting the α subunit of the interleukin (IL)-4 and IL-13 receptors, has been assessed in adults with moderateto-severe atopic dermatitis (AD). 1,2 Injection site reactions, nasopharyngitis, conjunctivitis, and transient increases in eosinophil counts from baseline were higher in the dupilumab groups than in the placebo groups in pivotal studies. 1,2 A recent study by Zhu et al 3 reported new regional dermatoses in 17 patients with AD trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 7 publications
2
48
2
1
Order By: Relevance
“…Despite IL‐4 levels being reported to be increased in some cases of SD, IL‐4 blockade might actually worsen SD. It has been proposed that specifically head and neck dermatitis, a well‐known side effect of dupilumab, might be due to increased levels of IL‐17 in lesional skin . In 2018, Wikramanayake et al demonstrated increased levels of IL‐17 expressing γδ T cells in Mpzl3 knockout mice.…”
Section: Future Directionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Despite IL‐4 levels being reported to be increased in some cases of SD, IL‐4 blockade might actually worsen SD. It has been proposed that specifically head and neck dermatitis, a well‐known side effect of dupilumab, might be due to increased levels of IL‐17 in lesional skin . In 2018, Wikramanayake et al demonstrated increased levels of IL‐17 expressing γδ T cells in Mpzl3 knockout mice.…”
Section: Future Directionsmentioning
confidence: 72%
“…This was the first time IL‐17 had been shown to be increased in SD . Th17 activity might be increased in SD at baseline, which could be worsened further with IL‐4 blockade . This is supported further by the fact that head and neck dermatitis responds to fluconazole in many cases.…”
Section: Future Directionsmentioning
confidence: 99%
“…Fewer serious/severe bacterial infections and other non-herpetic skin infections were observed among patients using dupilumab [ 33 ]. Among the side effects with long-term use of dupilumab, paradoxical erythema of the face, décolleté and neck, usually after 10–39 weeks of using dupilumab, has been reported [ 34 , 35 ]. In the group of adolescents > 12 years of age treated with dupilumab, a higher percentage of conjunctivitis and reactions at the injection site and lower rates of non-herpetic skin infections were observed [ 21 ].…”
Section: Biological Drugs In Atopic Dermatitismentioning
confidence: 99%
“…A multi-institution retrospective medical record review revealed that dupilumab-induced facial redness was seen in approximately 10% of patients treated with dupilumab in daily practice [12]. A French national retrospective study found that approximately 4% of patients taking dupilumab developed head and neck dermatitis [13]. A recent case report has suggested that this dupilumab-induced facial redness is attributable to hypersensitivity to Malassezia species and advocates for the use of oral itraconazole in the management of this symptom [14].…”
Section: Dupilumab (Dupixent®)mentioning
confidence: 99%